Potential Uses of Plant in Waru-waru and Teluk Semut Subregion, Sempu Island - Rahadiantoro, Apriyono; Danarto, Setyawan Agung (Proceeding International Conference on Global Resource Conservation, 2015)
Indonesia is the largest archipelago and one country with high biodiversity. The center of diversity is found on five largest islands include Sumatra, Java, Kalimantan, Sulawesi and Papua. Little is known about the potential use of plant Â Small island known susceptibility to the decline of biodiversity. In 2015, Purwodadi Botanic Garden have arranged plant assessnment in Waru-waru and Teluk Semut subregion, Sempu island. There are many plant collection have obtained but potential uses of plant have not been known. The purpose of this study was to know potential use of plant in Waru-waru and Teluk Semut Subregion, Sempu Island. The results showed that Waru-waru and Teluk Semut Subregion, Sempu Island has 100 plant species with potential use as medicine, food, timber, ornamental plants, and industry.Â Keywords: Potential uses of plant; Purwodadi Botanic Garden; Sempu island; Teluk Semut; Waru-waru